A 12-week community-based physical activity and mindfulness intervention: health outcomes and markers of autonomic nervous system function (Sweet Hearts biokinetics pilot study) - Evans, Robert William; Hume, David John; Noorbhai, Mohammed Habib; Van der Schyff, Nasief; Rauch, H.G. Laurie (SA Heart Journal, 2019)
The prevalence of non-communicable diseases (NCDs) has reached epidemic proportions in South Africa, coinciding with high levels of sedentary behaviour, urbanisation and stress. The nexus between stress, physical inactivity and non-communicable diseases may be regulated, in part, by changes in the autonomic nervous system (ANS). ANS function may be measured using a proxy of heart rate variability (HRV). Regular physical activity, controlled breathing and stress reduction have been shown to alter HRV. This paper presents preliminary data from a community-based biokinetics physical activity and mindfulness intervention (Sweet Hearts) on HRV. The study’s findings demonstrated favourable changes in measures of heart rate variability (HRV) – specifically in the low frequency (LF) spectrum that is associated with baroreflex function. The implications of these changes, in terms of health outcomes, along with efforts at addressing scalability and sustainability of community-based health promotion interventions may be important targets for future study.